Effect of number of baffles on flow and pressure drop in a shell side of a shell and tube heat exchangers - Sadikin, A.; Khian, N. Y.; Hwey, Y. P.; Al-Mahdi, H. Y.; Taib, I.; Sadikin, A. N.; Md Salleh, S.; Ayop, S. S. (Penerbit Akademia Baru, 2018)
The effect of number of baffles on flow and pressure drop on a shell side of shell-andtube heat exchangers was studied. In the present study, a set of CFD simulations using FLUENT version 17.0 from ANSYS were used to analyze the flow in the single shell and single tube pass heat exchangers consists of 20 mm diameter of tubes in staggered configuration with a variable number of baffles. The simulations were undertaken to inform on how the fluid flowed within the shell side of shell-and-tube heat exchangers. The results show that the variable number of baffles and baffle spacing in a heat exchanger strongly affect the flow pattern and pressure drop. This is consistent with other published data.